Konsep Keadilan Dalam Historiografi Melayu Islam Kurun ke-13 Sehingga ke-19 - Denisova, Tatiana (Afkar: Jurnal Akidah dan Pemikiran Islam, 2007)
The analysis of Malay Islamic historical texts from the thirteenth to the nineteenth centuries reveals much philosophical definitions therein. The Malay Muslim historical chronicles contain a lot of information and references about the concept of justice, the concept of governance (ruling) and the concept of punishment, all of which are closely connected with each other. The content analysis of reports about raja yang adil (the just or perfect ruler) from Malay Muslim his torical texts of thirteenth to the nineteenth centuries help us to interpret the definitions of justice wide spread in Malay society at that time. The results of this study clearly prove that in Malay Muslim historiography (as well as in Malay society at large) there existed already a comprehensive as well as general concept of justice. This article provides the selected texts that deal particularly with the issue of justice to gether with its analysis. The results of its study clearly proves that in Malay Muslim historiography (as well as in Malay society) in the thirteenth to the nineteenth centuries, there existed already a complete system of morality and ethics (akhlak and ta’dib) satisfying all the requirements of the Sunnah.